Cisplatin treatment reduces contraction to angiotensin II by altering expression of angiotensin II receptors: a pilot study - McSweeney, Kristen Renee; Gadanec, Laura Kate; Kubatka, Peter; Caprnda, Martin; Gaspar, Ludovit; Prosecky, Robert; Delev, Delian; Kruzliak, Peter; Apostolopoulos, Vasso; Zulli, Anthony (Molecular and cellular biochemistry, 2023)
The renin angiotensin system is a key regulator of blood pressure homeostasis. Angiotensin type 1 (AT1R) and 2 receptors (AT2R) have been investigated as targets for cisplatin-induced acute kidney injury; however, their therapeutic potential remains inconclusive. This pilot study aimed to determined the effect that acute cisplatin treatment had on angiotensin II (AngII)-induced contraction in blood vessels and expression profiles of AT1R and AT2R in mouse arteries and kidneys. Male C57BL/6 mice at 18 week of age (n = 8) were treated with vehicle or bolus dose of cisplatin (12.5 mg/kg). Thoracic aorta (TA), adnominal aorta (AA), brachiocephalic arteries (BC), iliac arteries (IL) and kidneys were collected for isometric tension and immunohistochemistry analysis. Cisplatin treatment reduced IL contraction to AngII at all doses (p < 0.01, p < 0.001, p < 0.0001); however, AngII did not induce contraction in TA, AA or BC in either treatment group. Following cisplatin treatment, AT1R expression was significantly upregulated in the media of TA (p < 0.0001) and AA (p < 0.0001), and in the endothelium (p < 0.05) media (p < 0.0001) and adventitia (p < 0.01) of IL. Cisplatin treatment significantly reduced AT2R expression in the endothelium (p < 0.05) and media (p < 0.05) of TA. In renal tubules, both AT1R (p < 0.01) and AT2R (p < 0.05) were increased following cisplatin treatment. Herein, we report that cisplatin reduces AngII-mediated contraction in IL and may be explained by an absence of normal counterregulatory expression of AT1R and AT2R, indicating other factors are involved.
Keywords: Male; zvířata; Mice, Inbred C57BL; receptor angiotensinu typ 2; mužské pohlaví; Angiotensin II; receptor angiotensinu typ 1; Mice; Receptor, Angiotensin, Type 1; pilotní projekty; Receptor, Angiotensin, Type 2; myši inbrední C57BL; cisplatina; Cisplatin; Animals; Pilot Projects; myši; angiotensin II